Goat’s Skim Milk Enriched with Agrocybe aegerita (V. Brig.) Vizzini Mushroom Extract: Optimization, Physico-Chemical Characterization, and Evaluation of Techno-Functional, Biological and Antimicrobial Properties - Danijel D. Milinčić; Ivana Sredović Ignjatović; Dejan Stojković; Jovana Petrović; Aleksandar Ž. Kostić; Jasmina Glamočlija; Ana Doroški Petković; Ana Plećić; Steva Lević; Vladislav Rac; Vladimir B. Pavlović; Slađana P. Stanojević; et al. (Foods)
The aim of this study was to develop a novel functional ingredient—goat’s skim milk enriched with Agrocybe aegerita (V. Brig.) Vizzini mushroom extract (ME/M)—using Central Composite Design (CCD). The optimized ME/M ingredient was evaluated for its physico-chemical, techno-functional, biological, and antimicrobial properties. Physico-chemical properties were analyzed using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and Dynamic Light Scattering (DLS). The ingredient exhibited a polymodal particle size distribution and contained glucans, along with a newly formed polypeptide resulting from the selective cleavage of goat milk proteins. A 0.1% ME/M solution demonstrated good emulsifying and foaming properties. Additionally, ME/M showed strong antiproliferative effects on human cancer cell lines, particularly Caco-2 (colorectal) and MCF7 (breast) cancer cells. The ingredient also promoted HaCaT cell growth without cytotoxic effects, suggesting its safety and potential wound-healing properties. Furthermore, the addition of ME/M to HaCaT cells inoculated with Staphylococcus aureus resulted in reduced IL-6 levels compared to the control (without ME/M), indicating a dose-dependent anti-inflammatory effect. The optimized ME/M ingredient also exhibited antibacterial, antifungal, anticandidal, and antibiofilm activity in one-fourth of MIC. These findings suggest that the formulated ME/M ingredient has strong potential for use in the development of functional foods offering both desirable techno-functional properties and bioactive benefits.